A dilemma between harmony and honesty: insights from indonesian university students on social presence in peer evaluation - Kristianto, Ignatius Indra; Harendita, Monica Ella (Universitas Merdeka Malang, 2024)
Peer evaluation can enhance learning outcomes, interpersonal skills, and student engagement in higher education. However, while factors like ability levels and gender influence peer evaluation dynamics, the role of social presence—projecting individual identities and connecting with peers—remains underexplored. Additionally, there is limited research on how culture affects peer evaluation in non-Western contexts, such as Indonesia. This study examines the intersection of social presence and peer evaluation in Indonesian higher education, focusing on students' perceptions, benefits, and challenges. Using a descriptive qualitative approach, the study involved surveys and interviews with 69 students in an English for Specific Purposes course at a private Indonesian university. After completing online peer evaluations, participants completed an online survey with closed- and open-ended questions. Five students were also interviewed for additional insights. The findings highlight that peer evaluation provided benefits such as changed perspectives, closer relationships, and opportunities for self-reflection. However, challenges, including reluctance to provide honest feedback, were also identified. From a sociocultural perspective, these challenges may relate to Indonesia’s collectivist culture. Recommendations for improving peer evaluation include conducting evaluations in class, justifying scores, and providing task evidence. This study emphasizes the potential of peer evaluation to enhance social presence and educational outcomes when properly guided and supported while also underscoring the importance of considering cultural context in its implementation.